Age and sex differences in numerical responses, dietary shifts, and total responses of a generalist predator to population dynamics of main prey - Masoero Giulia; Laaksonen Toni; Morosinotto Chiara; Korpimäki Erkki (SPRINGER, 2022)
Fluctuations in the abundance of main prey species might shape animal communities, by inducing numerical responses and dietary shifts in predators. Whether numerical responses and dietary shifts differ among individuals of different age and sex has so far gained little attention. These differences could affect how much predators consume main and alternative prey, thus causing variation in predation pressure on main and alternative prey species. We studied the effect of fluctuating main prey abundance (voles) in autumn on the age and sex composition of a food-hoarding population of Eurasian pygmy owls Glaucidium passerinum (327 individuals), and on the species composition of their food stores in western Finland during 2003-2017 (629 food stores). Numbers of yearlings (< 1-year old) of both sexes and adult (+ 1-year old) females increased with increasing vole abundance. During low vole abundance, adult owls stored more small birds and less small mammals than yearlings. Females stored more small mammals than males and showed a tendency to store less birds. The amount of consumed birds (the most important alternative prey), and in particular of crested, willow, great, and blue tits, increased with low vole densities. Our results show that numerical, functional, and total responses of pygmy owls, and probably also other vertebrate predators, to the availability of the main prey in winter are shaped by the age and sex composition of the predator population, which both show large spatio-temporal variation in boreal forests.